Isolation, characterization, and perspectives of use of stem cells from human exfoliated deciduous teeth (SHED) from children with cleft lip and palate - Santos, Mayara Bringel dos (2022)
This thesis aimed to present two scientific papers. Article 1 approached a review of studies using stem cells from human exfoliated deciduous teeth (SHEDs) in bone regeneration, highlighting the use in patients with cleft lip and palate (CLP). In Article 2, the objective was to compare the characterization of SHED between children with and without cleft lip and palate, to a view to analyzing whether autologous SHEDs may be considered as an option so that, soon, they can be used as an alternative in the reconstruction of alveolar clefts in patients with CLP. In Article 1, it was noted that in vitro and in vivo studies have been carried out so that bone regeneration can be performed with non-invasive materials, such as scaffolds and stem cells, including SHEDs. In vivo studies have shown that SHED can induce bone formation, produce dentin, and express neuronal markers. Although many efforts are being made because it is a promising alternative therapy that could bring benefits to the treatment and quality of life of many subjects, there are still few reports in the literature about its applicability, especially in subjects with CLP. In Article 2, dental pulp tissues were obtained from six healthy deciduous teeth in the exfoliation stage, from six donors aged between 4 and 12 years, and divided into two groups, without cleft lip and palate (Control Group) and with cleft lip and palate (Cleft Group). The cells obtained in the primary culture were analyzed immunophenotypically and collected those with positive expression of cell surface markers CD105, CD73, CD90 and negative for CD45, CD34, CD11b, CD19, HLA-DR (PE) after sorting in Flow Cytometry. The cells were subjected to multilineage differentiation and were morphologically analyzed. The difference immunophenotypic between groups was analyzed by Student\'s t-test, and the level of significance was set at 5% (p < 0.05). Plastic adhesion was demonstrated and high levels of MSC markers were identified in both groups, with positive expression of CD105, CD73, and CD90 (95% positive) and absence of hematopoietic lineage markers CD45, CD34, CD11b, CD19, and HLA- DR (2% positive). Pulp cells demonstrated adipogenic, osteogenic, and chondrogenic differentiation capacity. The morphological analysis identified a slightly smaller nucleus and proliferative capacity lower in the time evaluated in the Cleft group. There was a statistically significant difference (p=0.042) when comparing the SHEDs obtained after sorting from the two groups, being greater in the Cleft group. After confirming the standard criteria for defining multipotent MSCs in both groups, it was possible to confirm the isolation and characterization of SHED in all samples. These results suggest that SHEDs from children with CLP can be considered an option for future investigations into the autologous use of cells in therapeutic intervention. Notwithstanding, future studies are still needed to evaluate possible internal differences between cells, analyze the growth curve between groups and quantify osteogenic differentiation, aiming to identify whether the cleft could favor bone regeneration through tissue engineering.